2014
DOI: 10.1111/codi.12749
|View full text |Cite
|
Sign up to set email alerts
|

KRAS status and resistance to epidermal growth factor receptor tyrosine‐kinase inhibitor treatment in patients with metastatic colorectal cancer: a meta‐analysis

Abstract: All the results favoured a stronger link between mutant KRAS and anti-EGFR mAb, but due to a mutually exclusive relationship between KRAS and other gene mutations the clinical usefulness of KRAS mutation as a selection marker for sensitivity to EGFR TKIs in mCRC is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Previous studies have shown that tumors with high methylation status (called the CpG island methylation phenotype [CIMP] in previous studies) are closely associated with MSI‐high CRC . Thus, methylation status has been subclassified into two groups: CIMP‐high and CIM‐low . Although most studies have used one group of classifier markers, including original CIMP markers (the one‐panel method), Yagi and Kaneda recently used a two‐panel method and subclassified tumors into three groups: HME, IME, and LME.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that tumors with high methylation status (called the CpG island methylation phenotype [CIMP] in previous studies) are closely associated with MSI‐high CRC . Thus, methylation status has been subclassified into two groups: CIMP‐high and CIM‐low . Although most studies have used one group of classifier markers, including original CIMP markers (the one‐panel method), Yagi and Kaneda recently used a two‐panel method and subclassified tumors into three groups: HME, IME, and LME.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is relevant for the development of therapies for CRC because targeted biological agents, such as cetuximab, are influenced by KRAS mutations. (29) Therefore, tumors within this subgroup may not be affected by cetuximab therapy, a promising recent development in therapeutic options for CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAS and RAF gene mutations have been considered potential markers of sensitivity to MEK inhibition largely due to the constitutive activation of MEK seen in BRAF mutant cancer cells and to a lesser extent in KRAS mutant cells [ 17 , 18 ]. Thus, MEK has become a potential target for therapy given that mutation in these kinases has been identified as a negative predictor of benefit from EGFR inhibitor therapy [ 19 , 20 , 21 ]. However, acquired resistance after MEK inhibition seems inevitable.…”
Section: Cross-talk Between Mek and Pi3k Pathwaymentioning
confidence: 99%
“…The RAS protein exhibits intrinsic guanosine triphosphate (GTP) enzymatic activity, and is involved in cell proliferation, differentiation, and apoptosis by switching the mutual transformation regulatory signal system between guanosine diphosphate (GDP) and GTP. The KRAS gene has a high mutation rate in patients with colorectal cancer and lung cancer, and confers the resistance to epidermal growth factor receptor (EGFR), tyrosine kinase inhibitors (TKIs), and EGFR monoclonal antibody agents ( Chen et al , 2013 ; Li et al , 2014 ; Leiser et al , 2015 ; Hsu et al , 2016 ). Reports indicate that KRAS gene mutations in patients with non-small cell lung cancer are related to short survival time and poor prognosis ( Li et al , 2016 ; Tao et al , 2016 ).…”
Section: Introductionmentioning
confidence: 99%